Neuroanatomi klinik = (clinical neuroanatomy) / Richard S. Snell ; alih bahasa, Liliana Sugiharto ; editor, Lydia Djayasaputra, Carolina Salim - SNELL, Richard S.; Liliana Sugiharto; Lydia Djayasaputra; Carolina Salim (EGC, 2013)
xx, 560 hlm. ilus. 30 cm. (3 eks.)